Cytokinins in tobacco and wheat chloroplasts. Occurrence and changes due to light/dark treatment - Benková, Eva; Witters, Erwin; Van Dongen, Walter; Kolář, Jan; Motyka, Václav; Brzobohatý, Břetislav; Van Onckelen, Henri; Macháčková, Ivana (Plant Physiology)
Although cytokinins (CKs) affect a number of processes connected with chloroplasts, it has never been rigorously proven that chloroplasts contain CKs. We isolated intact chloroplasts from tobacco (Nicotiana tabacum L. cv SR1) and wheat (Triticum aestivum L. cv Ritmo) leaves and determined their CKs by liquid chromatography/tandem mass spectroscopy. Chloroplasts from both species contained a whole spectrum of CKs, including free bases (zeatin and isopentenyladenine), ribosides (zeatin riboside, and isopentenyladenosine), ribotides (isopentenyladenosine-5′-monophosphate, zeatin riboside-5′-monophosphate, and dihydrozeatin riboside-5′-monophosphate), and N-glucosides (zeatin-N 9-glucoside, dihydrozeatin-N 9-glucoside, zeatin-N 7-glucoside, and isopentenyladenine-N-glucosides). In chloroplasts there was a moderately higher relative amount of bases, ribosides, and ribotides than in leaves, and a significantly increased level ofN 9-glucosides of zeatin and dihydrozeatin. Tobacco and wheat chloroplasts were prepared from leaves at the end of either a dark or light period. After a dark period, chloroplasts accumulated more CKs than after a light period. The differences were moderate for free bases and ribosides, but highly significant for glucosides. Tobacco chloroplasts from dark-treated leaves contained zeatin riboside-O-glucoside and dihydrozeatin riboside-O-glucoside, as well as a relatively high CK oxidase activity. These data show that chloroplasts contain a whole spectrum of CKs and the enzymatic activity necessary for their metabolism.

Ionotropic Glutamate Receptors in the CNS
This volume provides an overview of glutamate receptors and their role in excitatory neurotransmission. It focusses on three aspects. First, it describes the functional, molecular, and pharmacological properties of glutamate receptors (AMPA, NMDA, and kainate receptors). Second, it gives a survey how these receptors are involved in synaptic transmission at different glutamatergic synapses in the mammalian CNS. Finally, it adresses how overactivation of glutamate receptors can lead to excitotoxic cell death, and emphasizes the importance of glutamate receptors as potential therapeutical targets. The chapters, written by leading scientists, give accurate summaries of facets that have emerged recently in this field. The book demonstrates the strength of a multidisciplinary approach involving physiology, pharmacology, and molecular biology. It will be useful for other scientists in and outside the field, lecturers and students at different educational levels.

A role for amontillado the Drosophila homolog of the neuropeptide precursor processing protease PC2 in triggering hatching behavior - Siekhaus, Daria E; Fuller, Robert (Journal of Neuroscience)
Accurate proteolytic processing of neuropeptide and peptide hormone precursors by members of the kexin/furin family of proteases is key to determining both the identities and activities of signaling peptides. Here we identify amontillado (amon), the Drosophila melanogaster homolog of the mammalian neuropeptide processing protease PC2, and show that in contrast to vertebrate PC2, amontillado expression undergoes extensive regulation in the nervous system during development. In situ hybridization reveals that expression of amontillado is restricted to the final stages of embryogenesis when it is found in anterior sensory structures and in only 168 cells in the brain and ventral nerve cord. After larvae hatch from their egg shells, the sensory structures and most cells in the CNS turn off or substantially reduce amontillado expression, suggesting that amontillado plays a specific role late in embryogenesis. Larvae lacking the chromosomal region containing amontillado show no gross anatomical defects and respond to touch. However, such larvae show a greatly reduced frequency of a hatching behavior of wild- type Drosophila in which larvae swing their heads, scraping through the eggshell with their mouth hooks. Ubiquitous expression of amontillado can restore near wild-type levels of this behavior, whereas expression of amontillado with an alanine substitution for the catalytic histidine cannot. These results suggest that amontillado expression is regulated as part of a programmed modulation of neural signaling that controls hatching behavior by producing specific neuropeptides in particular neurons at an appropriate developmental time.

Determining the redshift of reionization from the spectra of high‐redshift sources - Haiman, Zoltán; Loeb, Abraham (The Astrophysical Journal)
The redshift at which the universe was reionized is currently unknown. We examine the optimal strategy for extracting this redshift, zreion, from the spectra of early sources. For a source located at a redshift zs beyond but close to the reionization redshift, (1 + zreion) < (1 + zs) < 32/27(1 + zreion), the Gunn-Peterson trough splits into disjoint Lyα, Lyβ, and possibly higher Lyman series troughs, with some transmitted flux between these troughs. We show that although the transmitted flux is suppressed considerably by the dense Lyα forest at high redshifts, it could still be detectable as long as zreion ≲ 8. If the ionizing sources are bright and have a short duty cycle (e.g., if they are miniquasars or starbursts with a lifetime ≲106 yr), then breakthrough occurs shortly after the H II regions around them overlap, and the transmitted flux provides a measurement of zreion. The Next Generation Space Telescope will reach the spectroscopic sensitivity required for such a measurement.

X-ray emission from the first quasars - Haiman, Zoltán; Loeb, Abraham (The Astrophysical Journal)
It is currently unknown whether the universe was reionized by quasars or stars at z ≳ 5. We point out that quasars can be best distinguished from stellar systems by their X-ray emission. Based on a simple hierarchical CDM model, we predict the number counts and X-ray fluxes of quasars at high redshifts. The model is consistent with available data on the luminosity function of high-redshift quasars in the optical and soft X-ray bands. The cumulative contribution of faint, undetected quasars in our model is consistent with the unresolved fraction of the X-ray background. We find that the Chandra X-ray Observatory might detect ~10^2 quasars from redshifts z ≳ 5 per its 17' × 17' field of view at the flux threshold of ~2 × 10^-16 ergs s^-1 cm^-2. The redshifts of these faint point sources could be identified by follow-up infrared observations from the ground or with the Next Generation Space Telescope.

Models for dusty Lyα emitters at high redshift - Haiman, Zoltán; Spaans, Marco (The Astrophysical Journal)
Models are presented for the Lyα emission of dusty high-redshift galaxies by combining the Press-Schechter formalism with a treatment of the inhomogeneous dust distribution inside galaxies. It is found that the amount of Lyα radiation escaping from the galaxies strongly depends on the time over which the dust is produced through stellar activity and on the ambient inhomogeneity of the H II regions that surround the ionizing OB stars. Good agreement is found with recent observations, as well as with previous nondetections. Although a detailed determination of the individual model parameters is precluded by uncertainties, we find that (1) the dust content in primordial galaxies builds up in no more than ~5 × 108 yr, (2) the galactic H II regions are inhomogeneous with a cloud-covering factor of order unity, and (3) the overall star formation efficiency is at least ~5%. It is predicted that future observations can detect these Lyα galaxies up to redshifts of ~8. If the universe is reionized at zr ≲ 8, the corresponding decline in the number of Lyα emitters at z ≳ zr could prove to be a useful probe of the reionization epoch.

Formation of the first stars and quasars - Haiman, Zoltán (Advances in Space Research)
We examine various observable signatures of the first generation of stars and low-luminosity quasars, including the metal enrichment, radiation background, and dust opacity/emission that they produce. We calculate the formation history of collapsed baryonic halos, based on an extension of the Press-Schechter formalism, incorporating the effects of pressure and H2-dissociation. We then use the observed C/H ratio at z=3 in the Lyman-α forest clouds to obtain an average the star formation efficiency in these halos. Similarly, we fit the efficiency of black-hole formation, and the shape of quasar light curves, to match the observed quasar luminosity function (LF) between z=2−4, and use this fit to extrapolate the quasar LF to faint magnitudes and high redshifts. To be consistent with the lack of faint point-sources in the Hubble Deep Field, we impose a lower limit of ∼ 75 km s−1 for the circular velocities of halos harboring central black holes. We find that in a ΛCDM model, stars reionize the IGM at zreion=9−13, and quasars at z=12. Observationally, zreion can be measured by the forthcoming MAP and Planck Surveyor satellites, via the damping of CMB anisotropies by ∼10% on small angular scales due to electron scattering. We show that if reionization occurs later, at 5 ≲ zreion ≲ 10, then it can be measured from the spectra of individual sources. We also find that the Next Generation Space Telescope will be able to directly image about 1–40 star clusters, and a few faint quasars, from z >10 per square arcminute. The amount of dust produced by the first supernovae has an optical depth of τ=0.1−1 towards high redshift sources, and the reprocessed UV flux of stars and quasars distorts the cosmic microwave background radiation (CMB) by a Compton y-parameter comparable to the COBE limit, y ∼ 1.5 × 10^−5.

Constraints from the Hubble deep field on high‐redshift quasar models - Haiman, Zoltán; Madau, Piero; Loeb, Abraham (The Astrophysical Journal)
High-resolution, deep-imaging surveys are instrumental in setting constraints on semianalytical structure formation models in cold dark matter (CDM) cosmologies. We show here that the lack of unresolved B-band "dropouts" with V>25 mag in the Hubble Deep Field appears to be inconsistent with the number of "miniquasars" expected if massive black holes form with a constant universal efficiency in all CDM halos. To reconcile the models with the data, a mechanism is needed that suppresses the formation of active nuclei in halos with circular velocities vcirc≲50-75 km s-1. This feedback naturally arises because of the photoionization heating of the gas by the UV background. We consider several alternative effects that would help reducing the number of miniquasars and find that these cannot alone account for the observed lack of detections. If reddening by dust can be neglected at early epochs, consistency with the optical data also requires that the luminous extent of dwarf galaxies at high redshifts be larger than a few percent of the virial radii of their dark matter halos, in order not to overpredict the number of pointlike B-band dropouts. Future deep observations in the J and H bands with NICMOS might reveal several z≳5 objects per field or provide even stronger constraints on the models than existing B, V, and I data.

Molybdenum selenide molecular wires as one-dimensional conductors - Venkataraman, Latha; Lieber, Charles M. (Physical Review Letters)
Scanning tunneling microscopy (STM) has been used to characterize the structure and electronic properties of molybdenum selenide (Mo6⁢Se6) molecular wires. STM images resolve the 0.45 nm unit cell repeat in isolated molecular wires and bundles of wires. Tunneling spectroscopy measurements exhibit sharp peaks in the local density of states that are consistent with the Van Hove singularities expected for a one-dimensional (1D) system. These data have been compared with previous band structure calculations. Preliminary measurements at 5 K show no evidence of a gap opening at low temperatures. The implications of these results to metal-insulator transitions in 1D systems are discussed.

Radiative feedback from the first objects and the end of the cosmological dark age - Haiman, Zoltán (Astrophysics and Space Science)
In hierarchical models of structure formation, an early cosmic UV background(UVB) is produced by the small (T vir ≲ 104K) halos that collapse before cosmological reionization. If the sources in the first collapsed halos are stars, then their UV flux below 13.6 eV photo-dissociates the molecular hydrogen H2 in subsequently collapsing halos and causes a pause in the cosmic star-formation history. The buildup of the UVB, and reionization is delayed until larger halos (T vir ≳ 104K) collapse. In contrast, if the small halos host mini-quasars with hard spectra extending to∼1keV, then their X-rays balance the effects of the UVB, the negative feedback does not occur, and reionization can be caused early on by the small halos.

Models for high-redshift Lyα emitters - Haiman, Zoltán; Spaans, M. (AIP Conference Proceedings)
We present models for dusty high–redshift Lyα emitting galaxies by combining the Press–Schechter formalism with a treatment of inhomogeneous dust distribution inside galaxies. These models reproduce the surface density of emitters inferred from recent observations, and also agree with previous non–detections. Although a detailed determination of the individual model parameters is precluded by uncertainties, we find that (i) the dust content of primordial galaxies builds up in no more than ∼ 5 × 10^8 yr, (ii) the galactic HII regions are nhomogeneous with a cloud covering factor of order unity, and (iii) the overall star formation efficiency is at least ∼ 5%. Future observations should be able to detect Lyα galaxies upto redshifts of z ∼ 8. If the universe is reionized at zr ∼< 8, the corresponding decline in the number of Lyα emitters at z ∼> zr could prove to be a useful probe of the reionization epoch.

Empirical constraints on the first stars and quasars - Haiman, Zoltán; Loeb, A. (AIP Conference Proceedings)
Empirical studies of the first generation of stars and quasars in the Universe will likely become feasible over the next decade. The Next Generation Space Telescope will provide direct imaging and photometry of sub-galactic objects at (math formular) while microwave anisotropy experiments, such as MAP or Planck, will set constraints on the ionization history of the intergalactic medium due to these sources. We describe the expected signals that will be detectable with these future instruments.

Smooth muscle cells are the site of neurokinin-1 receptor localization in the arterial supply of the rat sciatic nerve - Kummer, Wolfgang; Shigemoto, Ryuichi; Haberberger, Rainer (Neuroscience Letters)
The occurrence and distribution of the preferred receptor for the neuropeptide, substance P (SP), the neurokinin-1 receptor (NK1R) was investigated in the vascular supply of the rat sciatic nerve. Messenger RNA for NK1R was demonstrated by RT-PCR in the epineurial layer where the majority of small arteries and arterioles feeding the endoneurial vasculature are located. Immunoreactivity to NK1R-protein was localized on the smooth muscle cells of these arterial vessels by means of immunofluorescence using a polyclonal NK1R antiserum. This muscular localization of NK1R explains the previously reported [Zochodne, D.W. and Ho, L.T., J. Physiol. 444 (1991) 615- 630] moderate vasoconstrictor rather than vasodilator effects of SP in this vascular bed.

Metabotropic glutamate receptor subtype 7 ablation causes deficit in fear response and conditioned taste aversion - Masugi, Miwako; Yokoi, Mineto; Shigemoto, Ryuichi; Muguruma, Keiko; Watanabe, Yasuyoshi; Sansig, Gilles; Van Der Putten, Herman; Nakanishi, Shigetada (Journal of Neuroscience)
Metabotropic glutamate receptors (mGluRs) consist of eight different subtypes and exert their effects or second messengers and ion channels via G- proteins. The function of individual mGluR subtypes in the CNS, however, largely remains to be clarified. We examined the fear response of freezing after electric shock in wild-type and mGluR7(-/-) knockout littermates. Wild- type mice displayed freezing immediately after and 1 d after footshock. In comparison, mGluR7(-/-) knockout mice showed significantly reduced levels in both immediate postshock and delayed freezing responses. However, the knockout mice exhibited no abnormalities in pain sensitivity and locomotor activity. To further examine amygdala-dependent behavior, we performed conditioned taste aversion (CTA) experiments. In wild-type mice, the administration of saccharin followed by intraperitoneal injection of the malaise-inducing agent LiCl resulted in an association between saccharin and LiCl. This association caused strong CTA toward saccharin n contrast, mGluR7(-/-) knockout mice failed to associate between the taste and the negative reinforcer in CTA experiments. Again, the knockout mice showed no abnormalities in taste preference and in the sensitivity to LiCl toxicity. These results indicate that mGluR7 deficiency causes an impairment of two distinct amygdala-dependent behavioral paradigms. Immunohistochemical and immunoelectron-microscopic analyses showed that mGluR7 is highly expressed in amygdala and preferentially localized at the presynaptic axon terminals of glutamatergic neurons. Together, these findings strongly suggest that mGluR7 is involved in neural processes subserving amygdala-dependent averse responses.

NK-1 receptor immunoreactivity in distinct morphological types of lamina I neurons of the primate spinal cord - Yu, Xiao; Zhang, En; Craig, Arthur; Shigemoto, Ryuichi; Ribeiro Da Silva, Alfredo; De Koninck, Yves (Journal of Neuroscience)
In cat and monkey, lamina I cells can be classified into three basic morphological types (fusiform, pyramidal, and multipolar), and recent intracellular labeling evidence in the cat indicates that fusiform and multipolar lamina I cells are two different types of nociceptive cells, whereas pyramidal cells are innocuous thermoreceptive-specific. Because earlier observations indicated that only nociceptive dorsal horn neurons respond to substance P (SP), we examined which morphological types of lamina I neurons express receptors for SP (NK-1r). We categorized NK-1r- immunoreactive (IR) lamina I neurons in serial horizontal sections from the cervical and lumbar enlargements of four monkeys. Consistent results were obtained by two independent teams of observers. Nearly all NK-1r-IR cells were fusiform (42%) or multipolar (43%), but only 6% were pyramidal (with 9% unclassified). We obtained similar findings in three monkeys in which we used double-labeling immunocytochemistry to identify NK-1r-IR and spinothalamic lamina I neurons retrogradely labeled with cholera toxin subunit b from the thalamus; most NK-1r-IR lamina I spinothalamic neurons were fusiform (48%) or multipolar (33%), and only 10% were pyramidal. In contrast, most (~75%) pyramidal and some (~25%) fusiform and multipolar lamina I spinothalamic neurons did not display NK-1r immunoreactivity. These data indicate that most fusiform and multipolar lamina I neurons in the monkey can express NK-1r, consistent with the idea that both types are nociceptive, whereas only a small proportion of lamina I pyramidal cells express this receptor, consistent with the previous finding that they are nonnociceptive. However, these findings also indicate that not all nociceptive lamina I neurons express receptors for SP.

The distribution of substance P receptor (NK1)-like immunoreactive neurons in the newborn and adult human spinal cord - Ding, Yu; Zheng, Heng; Wang, Dian; Xu, Jun; Gong, Liang; Lü, Yan; Qin, Bing; Shi, Juan; Li, Hua; Li, Ji; Shigemoto, Ryuichi; Kaneko, Takeshi; et al. (Neuroscience Letters)
Substance P receptor (i.e. NK1)-like immunoreactive (SPR-LI) neurons were observed in the newborn and adult human spinal cord. Substance P receptor-like immunoreactive neuronal cell bodies were seen most frequently in lamina I, and were scattered throughout the remaining laminae of the dorsal horn and the area around the central canal. Some neurons in the intermediolateral nucleus also showed weak immunoreactivity. The pattern of distribution of SPR-LI neurons in the adult spinal cord was essentially the same as that in the newborn spinal cord. However, SPR-LI neurons cell bodies were seen much more frequently in the newborn than in the adult dorsal horn, especially in lamina II.

mGluR7-like receptor and GABA(B) receptor activation enhance neurotoxic effects of N-methyl-D-aspartate in cultured mouse striatal GABAergic neurones - Lafon Cazal, Mireille; Viennois, Gaëlle; Kühn, Rainer; Malitschek, Barbara; Pin, Jean; Shigemoto, Ryuichi; Bockaërt, Joël (Neuropharmacology)
Presynaptic metabotropic glutamate receptors (mGluRs) of group III constitute possible targets for putative neuroprotective drugs acting against glutamate excitotoxic insults. Indeed, in glutamatergic cerebellar granule neurones in culture, high concentrations of L-2-amino-4-phosphonobutyrate (L-AP4, above 0.3 mM, thus activating mGluR7) inhibit NMDA-induced cell death. In contrast, in striatal cultures which are enriched in GABAergic neurones, we show that high concentrations of L-AP4 increased neuronal death in control as well as in NMDA-stimulated cultures. Moreover, similar results were obtained with the GABA(B)R agonist, baclofen. Both the neuroprotective effects in cerebellar granule cells and the neurotoxic effects in striatal neurones were mediated via Gi-Go-coupled mGluRs, suggesting that these effects were probably mediated by mGluR7a or b and GABA(B)R expressed in these neurones. In striatal neurones, we found that L-AP4 and baclofen inhibited both basal and NMDA-stimulated GABA release. These inhibitions of GABA release may be responsible for the increase in basal and NMDA-stimulated neuronal death. Indeed, blockade of GABA(A) receptors with bicuculline increased neuronal death of control and NMDA-treated striatal cultures. Taken together, these results suggest that L-AP4 and baclofen, via mGluR7 and GABA(B)R, reduced the neuroprotective effect of GABA present in striatal cultures acting via GABA(A) receptors. Although caution must be taken when extrapolating from in vitro to in vivo situations, the present experiments and the recent observations that mGluR7 and GABA(B)R are expressed in heterologous synapses, should be taken into consideration when evaluating the neuroprotective action of future mGluR7 specific agonists or GABA(B)R specific antagonists.

Spatial distribution of GABA(B)R1 receptor mRNA and binding sites in the rat brain^ - Bischoff, Serge; Leonhard, Sabine; Reymann, Nicole; Schuler, Valérie; Shigemoto, Ryuichi; Kaupmann, Klemens; Bettler, Bernhard (Journal of Comparative Neurology)
A γ-aminobutyric acid (GABA)(B) receptor (named GABA(B)R1) has been recently cloned in the rat and human brain and two variants generated by alternative RNA splicing were identified. In the present study, we addressed the question as to whether these variants contribute to the diversity of GABA(B) receptor-mediated physiological responses and constitute real receptor subtypes with distinct functions. To this aim, we have mapped the GABA(B)R1 (R1a) and GABA(B)R1b (R1b) transcript distribution in the rat brain using in situ hybridization. We have compared the mRNA distribution with the distribution of [ 3H]CGP54626-labeled binding GABA(B)R1 receptor sites as assessed in adjacent cryosections by quantitative autoradiography. We found that GABA(B) receptor transcripts and binding sites are expressed in the brain in almost all neuronal cell populations. Expression in glial cells, if any, is marginal. We observed a good parallelism between GABA(B)R1 mRNA transcripts and binding sites in broad neuroanatomical entities with highest densities in hippocampus, thalamic nuclei, and cerebellum. By contrast, R1a and R1b transcripts exhibit marked differences in their regional and cellular distribution pattern. A typical example is the cerebellum with an almost exclusive expression of R1b in the Purkinje cells and of R1a in the granule, stellate, and basket cells. Data pointing at a pre- versus postsynaptic localization for R1a and R1b, respectively, at some neuronal sites are presented.

Modulation of synaptic transmission and differential localisation of mGlus in cultured hippocampal autapses - Bushell, Trevor; Lee, Chong; Shigemoto, Ryuichi; Miller, Richard (Neuropharmacology)
Metabotropic glutamate receptors (mGlus) are known to modulate synaptic transmission in various pathways of the central nervous system, but the exact mechanisms by which this modulation occurs remain unclear. Here we utilise electrophysiological and immunocytochemical techniques on cultured autaptic hippocampal neurones to investigate the mechanism of action and distribution of mGlus. Agonists at all three groups of mGlus depressed glutamatergic transmission, whereas only agonists at group I mGlus depressed GABAergic transmission. Agonists at all mGlus failed to modulate Ca2+ and K+ channels in glutamatergic autapses whereas an agonist at group III mGlus did depress the frequency of miniature excitatory postsynaptic currents (mEPSCs). Agonists failed to modulate Ca2+ or K+ channels and miniature inhibitory postsynaptic currents (mIPSCs) in GABAergic autapses. Distribution studies using selective antibodies revealed punctate staining for group III mGlus that co-localised with the synaptic marker, synaptophysin. Staining for the remaining mGlus was more diffuse throughout the soma and processes with little co-localisation with synaptophysin. The distribution of the group III receptors is consistent with the direct 'downstream' modulation of mEPSCs, although the exact mechanism of action for the remaining receptors remains unclear.

An extension of the Artin-Mazur theorem - Kaloshin, Vadim (The Annals of Mathematics)
Keywords: Statistics; Probability and Uncertainty; Statistics and Probability